California Human Relations Commissions: A Survey of Needs, Capacities, and Interests - McDonald, Kim; Downey, Dennis (CBR@CSUCI: An annual volume of community-based research, 2019)
Research was conducted as a service-learning capstone project in partnership with the California Association of Human Relations Organizations (CAHRO). The purpose was to gather information relevant to CAHRO’s mission of serving and strengthening our state’s local human relations commissions (HRCs), and to explore the feasibility of creating service-learning partnerships between HRCs and California State University campuses (through their respective Centers for Community Engagement). Responses to an online survey were received from 30 of California’s 43 active HRCs. Key findings are presented in the area of resources, key issues addressed, populations served, and interest in engaging in specific statewide initiatives (including an anti-hate crime network, CAHRO’s statewide bulletin, and proposed human relations / service learning partnerships).